Assessment of Awareness and Acceptance of the Human Papillomavirus Vaccine among Women in Saudi Arabia: A Community-Based Survey - Mishari M. Alrashidi; Ahmed K. Ali; Elhadi Miskeen; Abdulaziz D Algarni; Rawabi S Almatrafi; Naif S Albudyri; Tarig A Alrashidi (IMR Press, 2024)
Background: Globally, cervical cancer represents a major public health concern. The Human Papillomavirus (HPV) vaccine serves as a primary preventive strategy against cervical cancer. This study aimed to assess the HPV vaccine awareness and acceptability (HPVVAA) among women in Saudi Arabia. Methods: This study employed a mixed-methods approach, combining both qualitative and quantitative data to assess HPVVAA among women in Saudi Arabia. A national survey was conducted with a diverse sample of 640 Saudi women, aged 18 to 65, representing both urban and rural areas. Data collection involved structured questionnaires, including both closed-ended and open-ended questions, distributed online and via paper-based self-administration. Descriptive statistics summarized demographic characteristics, while inferential statistics and logistic regression were used to identify associations between variables. Thematic content analysis of the open-ended responses was conducted to explore recurring themes related to awareness, acceptability, and potential barriers. Statistical significance was set at p < 0.05. Ethics approval and written informed consent were obtained prior to participants' involvement in the study. Results: A total of 640 women participated in the study. The majority of participants were over 50 years old (31.2%), married (45.3%), and held a university or higher educational level (43.8%). Approximately 39.1% of participants had received the HPV vaccine, while 56.3% expressed willingness to accept it. Awareness of HPV and its link to cervical cancer was reported at 78.8% and 62.5%, respectively. The primary source of information (34.4%) was healthcare professionals. Positive attitudes toward vaccinations and favorable perceptions of the HPV vaccine's safety and efficacy were prevalent among the respondents. Age (p < 0.01; odds ratio [OR]: 1.134; 95% confidence interval [95% CI]: 1.045-1.231) and marital status (p = 0.027; OR: 1.078; 95% CI: 1.007-1.153) were significant predictors of vaccine acceptance. Age was identified as a significant factor that influences awareness (p < 0.001; OR: 1.25; 95% CI: 1.10-1.42). Participants who were one year older were 1.25 times more likely to be aware of the HPV vaccine, with a 95% CI of 1.10 to 1.42 (p < 0.001). Participants with better healthcare access were more likely to be aware of the HPV vaccine (p < 0.001; OR: 1.30; 95% CI: 1.15-1.47). Conclusions: The study found a significant HPVVAA among women in Saudi Arabia. However, there is room for improvement in vaccine uptake, particularly in addressing barriers such as accessibility, affordability, and fear of side effects. Targeted communication strategies and public health initiatives are recommended to enhance HPVVAA and uptake, ultimately contributing to the global goal of cervical cancer prevention and control.